2017
DOI: 10.1093/cid/cix497
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Maternal Influenza Vaccination Against All-Cause Lower Respiratory Tract Infection Hospitalizations in Young Infants: Results From a Randomized Controlled Trial

Abstract: SummaryInfluenza vaccination during pregnancy decreased the incidence of acute lower respiratory tract infection hospitalizations in infants born to vaccinated mothers. The benefits of protecting against influenza virus infection during early infancy might extend beyond protecting only against influenza-confirmed illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…Pregnant women are considered by the WHO as the main high‐risk group during pandemics. Maternal immunization can reduce the risk of post‐natal infections in the infants . Currently, two studies among pregnant women are ongoing in Tunisia and Saudi Arabia.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Pregnant women are considered by the WHO as the main high‐risk group during pandemics. Maternal immunization can reduce the risk of post‐natal infections in the infants . Currently, two studies among pregnant women are ongoing in Tunisia and Saudi Arabia.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The need to protect neonates and infants in the first 6 months of life from influenza is so important that many health authorities have recommended influenza vaccinations of pregnant women [49][50][51]. Studies have shown that vaccination during pregnancy is effective in reducing influenza cases for at least one influenza season [52,53].…”
Section: Influenza Vaccinationmentioning
confidence: 99%
“…Studies varied by study design, vaccine type (inactivated influenza vaccine, IIV3; live attenuated influenza vaccine, LAIV) and study population (Table 1). 16 were from South Africa, [11][12][13][14][16][17][18][19]23,25,[27][28][29][30][31][32] two each from Gabon 21,22 and Kenya, 20,26 and one study each from Mali 15,33 Senegal 24 and The Gambia. 33 The following study populations were identified: pregnant women (6 studies), children (6), elderly (3), HIV-Positive adults (1), healthcare workers (1) and all age groups (6).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…One RCT from South Africa 11 and one from Mali 15 evaluated influenza vaccination in pregnant women, with three studies reporting secondary analyses from the South Africa RCT [12][13][14] and one study reporting a secondary analysis from both RCTs (Supplementary table 1). 31 A single centre, randomised, double-blind placebo-controlled trial including HIV-uninfected and HIV-infected pregnant women (60% on HAART at enrolment, median CD4 count 393•5 cells/mm 3 ) was conducted in South Africa.…”
Section: Influenza Vaccination In Pregnant Womenmentioning
confidence: 99%